Evolution of Party Systems: New Point of Bifurcation? - E. G. SOLOVYEV (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
In face of the relative success of the right and left populists, among  representatives of the intellectual elite on the West arose a  conviction – in order to restore the liberal order and prevent the final victory of populists, traditional parties will have to make not  only rebranding. They must develop policies through which  globalization can serve the middle and working class. In fact, the  problem is even wider than the opposition to the right and left populists. The transformation of party systems takes place in the  context of the effects of globalization, generating new lines of  social tensions and divisions in society (including “globalized elite” –  “anti-globalistminded masses” opposition); under framework of  democracy deficit, when a significant part of the electorate of  developed Western countries clearly realizes that they “can change  the government, but not the policy” and from time to time under the influence of situational factors involve in the “protest voting”, in  support of alternative to political establishment political forces; in the context of fragmentation of the political field due to the crisis  of “Grand ideological narratives” and the appearance of so called  “molecular ideologies” and “one question” parties. Entering the  political arena in a number of countries of the far right and far left  forces is rather situational, but it becomes a consequence of the  current crisis trends – the migration crisis, terrorism, economic  recession. The rise of populist parties of all kinds (right, left, right- left) has its limits. But the process of party systems adaptation to a  new type of conflict between the globalized postmodern elites and  the majority of “nationalized” citizens of national states is only  developing now (both in developed and developing countries). The  question is in which degree the party and political systems of  different countries are ready to it and how the modern political elites  are flexible and adaptive to a new political challenge.